The importance of studying home economics in developing family life (Journal of the College of Basic Education, 2025)
Home economics in the field of family relations is concerned with programs of understanding, dialogue, democracy, etiquette, and respect for differences; whether in gender, color, religion, or upbringing, and its relationship to a strong, cohesive society capable of progress. Child rearing is considered one of the most important axes of study in home economics, and this includes the rights of the child from all aspects, and methods of raising and educating him. This field is concerned with developing the necessary life skills for the individual; whether mental, manual, or social skills. The current research gains its importance in that it addresses the importance of teaching home economics in the development of the family. The researcher hopes that it will fill a gap in the educational field and benefit from it in other studies that serve home economics subjects, in addition to improving the quality of teaching by highlighting a strategy that may be unknown to many teachers. Shedding light on it may also help motivate people to try it and benefit from its positives.